Recommendations for the management of elevated intraocular pressure due to bleb fibrosis after XEN gel stent implantation - Vera, Vanessa (Clin Ophthalmol, 2019)
Surgical management of glaucoma offers a means of effective disease control. A gel stent that facilitates drainage to the subconjunctival space offers intraocular pressure (IOP) reduction similar to traditional glaucoma filtering surgeries in a less invasive manner. However, like all subconjunctival filtering procedures that result in a bleb, fibrosis can present as a cause of elevated IOP. The following proposed techniques and recommendations for managing elevated IOP due to bleb fibrosis after gel stent implantation are based on the clinical experience of the authors. The goal of this paper is to improve outcomes following gel stent surgery by providing guidance on assessment of bleb function and strategies for bleb enhancement.